Uji Daya Hambat Ekstrak Daun Jambu (Psidium guajava) Terhadap Pertumbuhan Jamur Candida albicans Secara In Vitro - Nasution, Dina Rahmi Solihad; Ginting, Dedi Landani; Lubis, Yuni Aflah; Nasution, Izmi Fadhilah; Hasibuan, Elmi Sariani (Universitas Aufa Royhan, 2024)
Fungi are one of the microorganisms that cause disease in humans. A disease caused by fungi in humans is called mycosis. Types of mycosis are divided into two, namely superficial mycosis and systemic mycosis. Superficial mycosis is an infection by fungi that spread on the surface of the body only, while systemic mycosis is an infection by fungi that attack the entire body. One type of pathogenic fungus is Candida albicans which causes canker sores, vaginal discharge, skin irritation to cancer. This study aims to determine the effect of guava leaf extract (Psidium guajava) on the growth of Candida albicans fungi. This type of research is purely experimental. Guava leaf extract (P.guajava) was obtained by maceration technique using 96% ethanol solvent. Inhibitory power testing of extracts using the Kibry-Bauer method with blank discs. Candida albicans was obtained from the Microbiology Laboratory of FMIPA USU. The results of the study obtained the diameter of the inhibitory zone of guava leaf extract against the growth of Candida albicans fungus 14.6 mm at a concentration of 100% guava leaf extract which is classified as a strong inhibitory zone criterion